Biological activity of native Myrtaceae fruits from Chile as a potential functional food. Issue 12 (15th June 2022) - Velásquez, Patricia; Orellana, Jocelyn; Muñoz-Carvajal, Eduardo; Faúndez, Mario; Gómez, Miguel; Montenegro, Gloria; Giordano, Ady
Abstract: Myrtaceae fruits ( Myrceugenia obtusa, Luma apiculata, and Luma chequen ) were used as food and medicine by Chilean indigenous people. This study aimed to evaluate the bioactive properties of these berry-type fruits. The antioxidant capacity determined by the FRAP assay varied between 10.4 and 646.9 mmol Fe +2 /g, while the antibacterial activity against Staphylococcus aureus and Salmonella typhi was 0 − 33 mm and 0 − 7.33 mm, respectively. All the extracts were rich in polyphenols and showed low cytotoxicity. Overall, M. obtusa presented dissimilar results compared to those of L. apiculata and L. chequen, encouraging the use of these native fruits as food, nutraceutical, or pharmacological ingredients. Graphical Abstract: UF0001